Productive and reproductive performances of Sheep at field level of Rajshahi and Mymensingh District of Bangladesh - Mansur, Md Abdullah Al; Alam, Md Golam Shahi; Jha, Pankaj Kumar; Rimon, Md Asaduzzaman; Naher, Nazmun; Bari, Farida Yeasmin (Asian Journal of Medical and Biological Research, 2018)
This study was undertaken to assess the reproductive performances of sheep at field level of Rajshahi and Mymensingh district of Bangladesh during January to December, 2016. A total of 52 farms (26 each in Rajshahi and Mymensingh) were selected for determining the reproductive parameters of ewes. Ewe lambs in Mymensingh reached puberty at significantly (P<0.03) younger age (186.9±18.4 days) than in Rajshihi (199.9±24.9 days). The average age at first pregnancy was 201.4±20.0 days in two regions. Similarly, the ewes in Mymensingh was lambing at significantly (P<0.002) early age than ewes in Rajshahi (356.0±6.8 days vs. 372.7±27.8 days). The observed duration of oestrus at Rajshahi and Mymensingh was 36.0±6.7 hrs and 36.0±7.3 hrs, respectively. The gestation length varied from 145 to 150 days. The average gestation length was 147.9±3.4 days in two regions. The gestation length was not significant (P˃0.05) in the ewes between Rajshahi and Mymensingh (148.7±3.4 and 147.1±3.2 days; respectively). The pooled over litter size was 1.6±0.2 in two regions. However, there was no significant (P>0.05) difference in litter size of ewes in Rajshahi and Mymensingh region (1.7±0.2 vs. 1.6±0.2). The pooled lambing interval was 193.9±21.7 days in two regions. Mean birth weights of lambs, weaning weight and mature weight were 1.7±0.6 vs. 1.3±0.1 kg; 8.9±2.7 vs. 6.9±1.0 kg and 24.9±7.3 vs. 19.4±2.7 kg in Rajshahi and Mymensingh, respectively. These reproductive parameters were significantly higher (P<0.001) in Rajshahi compared with in Mymensingh. The reproductive parameters are almost similar between confined and the traditional management system if the farms are well managed. Asian J. Med. Biol. Res. March 2018, 4(1): 63-68